Development and Validation of a Scoring System for Predicting Periprocedural Complications During Percutaneous Coronary Interventions of Chronic Total Occlusions: The Prospective Global Registry for the Study of Chronic Total Occlusion Intervention (PROGRESS CTO) Complications Score - Barbara Anna Danek; Aris Karatasakis; Dimitri Karmpaliotis; Khaldoon Alaswad; Robert W. Yeh; Farouc A. Jaffer; Mitul P. Patel; Ehtisham Mahmud; William L. Lombardi; Michael R. Wyman; J. Aaron Grantham; Anthony Doing; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundHigh success rates are achievable for chronic total occlusion (CTO) percutaneous coronary intervention (PCI) using the hybrid approach, but periprocedural complications remain of concern. Although scores estimating success and efficiency in CTO PCI have been developed, there is currently no available score for estimation of the risk for periprocedural complications. We sought to develop a scoring tool for prediction of periprocedural complications during CTO PCI. Methods and ResultsWe analyzed data from 1569 CTO PCIs in the Prospective Global Registry for the Study of Chronic Total Occlusion Intervention (PROGRESS CTO) using a derivation and validation sampling ratio of 2:1. Variables independently associated with periprocedural complications in multivariable analysis in the derivation set were assigned points based on their respective odds ratios. Forty‐four (2.8%) patients experienced complications. Three factors were independent predictors of complications and were included in the score: patient age >65 years, +3 points (odds ratio, OR=4.85, CI 1.82‐16.77); lesion length ≥23 mm, +2 points (OR=3.22, CI 1.08‐13.89); and use of the retrograde approach +1 point (OR=2.41, CI 1.04‐6.05). The resulting score showed good calibration and discriminatory capacity in the derivation (Hosmer‐Lemeshow χ2 6.271, P=0.281, receiver‐operating characteristic [ROC] area=0.758) and validation (Hosmer‐Lemeshow χ2 4.551, P=0.473, ROC area=0.793) sets. Score values of 0 to 2, 3 to 4, and ≥5 were defined as low, intermediate, and high risk of complications (derivation cohort 0.4%, 1.8%, 6.5%, P<0.001; validation cohort 0.0%, 2.5%, 6.8%, P<0.001). ConclusionsThe PROGRESS CTO complication score is a useful tool for prediction of periprocedural complications in CTO PCI. Clinical Trial RegistrationURL: http://www.clinicaltrials.gov. Unique identifier: NCT02061436.